2017
DOI: 10.1055/s-0043-117401
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life after peroral endoscopic myotomy remains compromised in patients with achalasia type III

Abstract: Peroral endoscopic myotomy (POEM) is an excellent endoscopic treatment for achalasia. Clinical and manometric parameters are used for evaluation and follow-up. However, clinical success does not guarantee high quality of life (QoL) scores, generating doubts about their direct relationship. We aimed to evaluate QoL scores before and after POEM at medium and long term, to evaluate differences between achalasia subtypes and find which factors related to low QoL scores. Achalasia-confirmed patients undergoing POEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 34 publications
0
55
0
1
Order By: Relevance
“…52 With regard to POEM treatment, 3 of the 7 studies reported that achalasia type III was associated with failure. [53][54][55] Two Botox studies described that vigorous achalasia was found to be a predictor of good response. 25,56 Other manometric factors.…”
Section: Diagnostic Predictorsmentioning
confidence: 99%
“…52 With regard to POEM treatment, 3 of the 7 studies reported that achalasia type III was associated with failure. [53][54][55] Two Botox studies described that vigorous achalasia was found to be a predictor of good response. 25,56 Other manometric factors.…”
Section: Diagnostic Predictorsmentioning
confidence: 99%
“…Thin-POEM was effective in the short-term (12 months), confirmed by a decrease in the Eckardt score, IRP, and improved TBE emptying, which is comparable with standard POEM [1,2,5]. Two recurrences were found (both in type III patients), probably related to the different pathophysiology from the other types [13].…”
Section: Discussionmentioning
confidence: 59%
“…Our dual-POEM success rate is better than one reported by Werner; this suggests that dual-POEM may indeed have the advantage in mitigating the risk of recurrence, avoiding a repeat procedure. As for the patient (type III) who developed recurrence, a different pathophysiology from a different manometric subtype is one of the likely explanations [ 17 ]. However, given our limited number of patients and relatively short follow-up time, further studies with longer follow-up duration are needed to clarify this phenomenon in type III achalasia.…”
Section: Discussionmentioning
confidence: 99%